Perancangan Stasiun Menyetrika yang Ergonomis untuk Penyedia Jasa Penatu Rumahan dengan Pendekatan Antropometri dan Quality Function Deployment - Leony, Florence; Halim, Winda; Suhada, Kartika; Tjahjadi, Kevin (Jurnal Rekayasa Sistem Industri, 2025)
Laundry services are still used by many people, indicated by its existence, especially in office areas and universities. Not only they offer clothes washing but also ironing such that the clothes are ready to wear directly by consumers. Ironing is a process that requires the longest time so that the workload of the operators is heavier than operators in other work stations. As repetitive force is required in controlling the iron, they need supportive facilities to lessen the burden to the body. Moreover, the narrow working space especially for small, medium enterprises (SMEs) does not allow them to take a seat for while working, leading to fatigue and sores. Motivated by this, through this research we designed an ergonomic facility for ironing work station in laundry shops. We employed Quality Function Deployment method for product development that takes what kind of support the customer needs into account, as well as anthropometry approach to ensure the comfort of the user. Design process consists of four common steps of Ulrich and Eppinger, namely planning, concept development, system-level design, and detail design, while the latter step of testing and refinement was not employed as the product is in the form of 3D prototype. The pilot study found complaints from ironing station operators of several stores due to the inadequate facilities. In this research, the design process involved uncovering main requirements along with supporting needs which are then translated into an ergonomic and multifunctional ironing facility for laundry services belonging to SMEs as the user-centric solution. That is, space saving and comfortable for the operators as well as reduce the risk of musculoskeletal disorder.